Analisis Qualitiy of Service (QoS) Jaringan Internet Menggunakan Metode Action Research Pada Balai Diklat Keagamaan Palembang - Yevi Grata Putra; Tata Sutabri (Jurnal Sistem Informasi dan Ilmu Komputer, 2024)
Palembang Religious Education and Training Center as an education and training institution utilizes information technology, especially wifi internet networks to support various learning and training activities. To support these needs, a quality internet network is needed, so an evaluation and measurement of Quality of Service (QoS) is needed, because QoS is able to measure various important parameters in the network, such as throughput, delay, jitter, and packet loss, all of which play an important role in ensuring the network functions properly. The standard used is TIPHON. By using the Action Research method, this research will produce real internet quality data in accordance with actual conditions. After testing, the average results on the 4 parameters tested obtained an index value of 3. So that the overall quality of the internet network at the Palembang Religious Education and Training Center has good network quality.